Conflicting interpretations and FDA reputation: the case of post-market surveillance of breast implants - Maor, Moshe; Shoenfeld, Yehuda (Frontiers in Medicine, 2024)
Conflicting interpretations regarding the severity of the adverse effects associated with FDA-approved drugs and therapies are common among the US Food and Drug Administration (FDA), the medical community, patients, and the general public. However, scholars have paid little attention to how these conflicting interpretations may affect the FDA's reputation for facilitating inclusive dialogue between competing policy actors. Focusing on breast implants, a medical device characterized by a stormy regulatory past, we observe that the design properties of post-market surveillance are adjusted to lowquality information. Such information-gathering mechanisms likely lead to underreporting by medical practitioners and the public, thus resulting in low-quality data. Given that the FDA cannot rely on congressional appropriations to ensure a stable flow of funding, the confusion and uncertainty created by conflicting interpretations enhance the FDA's ability to appeal to different audiences simultaneously and thereby secure funding from industry-based user fees. This strategy may persist until the FDA's reputation is challenged by critical information regarding adverse effects and the ensuing potentially negative media coverage. A stable appropriation-based funding model will likely encourage stronger post-market surveillance of medical devices.